Effect of napier grass supplemented with Gliricidia sepium, Sapindus rarak or Hibiscus rosa-sinensis on in vitro rumen fermentation profiles and methanogenesis - Yuliana, P.; Laconi, E. B.; Jayanegara, A.; Achmadi, S. S.; Samsudin, A. A. (Diponegoro University, 2019)
This study examined the supplementation effects of gliricidia leaves(GL, Gliricidia sepium), lerak fruit(LF, Sapindus rarak), or hibiscusleaves(HL, Hibiscusrosa-sinensis) on in vitro rumen fermentation and methanogenesis and made a comparisonwith the Napier grass (NG, Pennisetum purpureum) grass. In vitro rumen fermentation was designed according to a randomized complete block design with four replications and seven treatments: NG, GL, LF, HL, NG 70% + GL 30%, NG 70% + LF 30%and NG 70% + HL 30%. The generated data were subjected to analysis of variance (ANOVA) with Duncan’s multiple range test and compared among treatment means.Addition of a plant containing saponin such as LF or HL to NG did not alter gas production after 24 and 48 h of incubation period in comparison to NG alone.The HLalone or blended with NGproduced the highest IVOMDduring the fermentation processas compared to other treatments (P<0.05). Adding LF supplement either singly or in combination significantly (P<0.05) reduced methane production in terms of %TVFA as compared to NG. Supplementation of LF plants has shifted VFA proportion towards more propionate and less acetate. The microbial population of LF, whether single or in combination had a tendency to reduce the rumen protozoa population but had no effect on methanogen population. It can be concluded that utilization of saponin-rich materials is particularly beneficial for reducing ruminal methane emission.